Electroacupuncture Attenuates CFA-Induced Inflammatory Pain by Regulating CaMKII - Yixiao Gu; Shuangdong Chen; Yunchang Mo; Yingying Tu; Na Chen; Xiaoyong Zhao; Shan Li; Qimin Yu; Qinxue Dai; Junlu Wang (Neural Plasticity)
Ca2+/calmodulin-dependent protein kinase II (CaMKII) is a multifunctional serine/threonine kinase that is ubiquitously distributed in the central and peripheral nervous systems. Moreover, its phosphorylated protein (P-CaMKII) is involved in memory, mood, and pain regulation in the anterior cingulate cortex (ACC). Electroacupuncture (EA) is a traditional Chinese therapeutic technique that can effectively treat chronic inflammatory pain. However, the CaMKII-GluA1 role in EA analgesia in the ACC remains unclear. This study investigated the role of P-CaMKII and P-GluA1 in a mouse model of inflammatory pain induced by complete Freund’s adjuvant (CFA). There were increased P-CaMKII and P-GluA1 levels in the ACC. We found that intracerebroventricular injection of KN93, a CaMKII inhibitor, as well as EA stimulation, attenuated complete Freund’s adjuvant-induced pain behavior. Further, EA increased pCaMKII-PICK1 complex (abbreviated as C-P complex) levels. Our findings demonstrate that EA inhibits inflammatory pain by inhibiting CaMKII-GluA1 phosphorylation. P-CaMKII is involved in EA analgesia as the pCaMKII-PICK1 complex.